The effect of pasteurisation on the composition of expressed human milk from HIV positive mothers, and its adequacy in relation to the growth of their very low birth weight premature infants - Van Wyk, Elisna (Stellenbosch : Stellenbosch University, 2008)
Thesis (MNutr (Interdisciplinary Health Sciences. Human Nutrition))--Stellenbosch University, 2008.